Cranberry Effects 0.05% on the Dental Biofilme of Individuals with Disabilities - Barreto, Jeisielle Alves da Anunciação; Trindade, Karina Melo; Barrientos, Marcia Otto; Ramos Souza e Souza, Samia (ARCHIVES OF HEALTH INVESTIGATION, 2023)
In this study we investigated the effectiveness of a 0.05% cranberry gel formulation in controlling microbial biofilm on dental surfaces of individuals with disabilities. The study included 26 individuals with disabilities. Using revealing pads, the microbial biofilm of the index tooth surfaces was stained. This staining was performed before and after application of a 0.05% cranberry gel formulation, which was applied for 7 to 15 days. The microbial biofilm differences found in all stages were described as mean and standard deviation and statistically evaluated. The biofilm control evaluated before the intervention with cranberry 0.05% showed an average of 1.76 ± 0.70. The formulated gel generated a positive mean drop to 0.98 ± 0.55 (p< 0.001). Cranberry gel 0.05% showed statistically significant improvements in microbial biofilm control.